The heterogeneous coma of comet 67P/Churyumov-Gerasimenko as seen by ROSINA: H 2 O, CO 2, and CO from September 2014 to February 2016 - Hoang,M; Altwegg,K; Balsiger,H; Beth,A; Bieler,A; Calmonte,U; Combi,MR; De,Keyser J; Fiethe,B; Fougere,N; Fuselier,SA; Galli,A; et al. (Astronomy and Astrophysics, 2017)
Context. The ESA Rosetta mission has been investigating the environment of comet 67P/Churyumov-Gerasimenko (67P) since August 2014. Among the experiments on board the spacecraft, the ROSINA experiment (Rosetta Orbiter Spectrometer for Ion and Neutral Analysis) includes two mass spectrometers to analyse the composition of neutrals and ions and a COmet Pressure Sensor (COPS) to monitor the density and velocity of neutrals in the coma. Aims. We study heterogeneities in the coma during three periods starting in October 2014 (summer in the northern hemisphere) and ending in February 2016 (end of winter in the northern hemisphere). We provide a detailed description of the main volatiles dynamics (H2O, CO2, CO) and their abundance ratios. Methods. We analysed and compared the data of the Reflectron-Type Time-Of-Flight (RTOF) mass spectrometer with data from both the Double Focusing Mass Spectrometer (DFMS) and COPS during the comet escort phase. This comparison has demonstrated that the observations performed with each ROSINA sensor are indeed consistent. Furthermore, we used a Direct Simulation Monte Carlo (DSMC) model to compare modelled densitites with in situ detections. Results. Our analysis shows how the active regions of the main volatiles evolve with the seasons with a variability mostly driven by the illumination conditions; this is the case except for an unexpected dichotomy suggesting the presence of a dust layer containing water deposited in the northern hemisphere during previous perihelions hiding the presence of CO2. The influence of various parameters is investigated in detail: distance to the comet, heliocentric distance, longitude and latitude of sub-satellite point, local time, and phase angle.